Análise setorial por meio da sinestesia em diferentes alimentos e para consumidores de diferentes nacionalidades - Oliveira, Mirella Cais Jejcic de (2016)
Companies need to innovate continuously to maintain market leadership. When the market is overloaded, the challenge is to create innovative products to attract and satisfy consumers. The overall objective of this study is to understand the behavior of consumers of red wine, coffee and beef based on sensory perception, when subjected to stimuli with attributes so when stimulated with different products and different stages of consumption. Consumers in different countries tested the chosen products. First, it conducted a quantitative study in Italy explored with red wine and the possible variations of sensory perceptions of the product through the five senses. The second study was qualitative and performed with form of coffee to address different consumer perceptions of the same age from different nationalities. Finally, the third study was qualitative and performed with beef in Boutique meat with consumers in São Paulo. The results showed that sensory analysis is an important indicator of food quality and therefore can create differentiation through improved sensory characteristics and improve the communication on the sensory attributes to consumers. There was no difference between the perceptions of consumers in different countries. The theoretical contribution of the study was to cover the gap theme sensory analysis.